¿Es necesario seguir un ritual? explorando los usos sociales de los medios de comunicación - Bent Steeg Larsen; Thomas Tufte (Estudios sobre las Culturas Contemporáneas)
Has media use anything to do with rituals? This question has not gone unanswered in media research. And there is much evidence that some kinds of media use actually liave the fonn and the functions of rituals. Most notably, perhaps, are the so called media events (royal weddings, Olympic Games, state funerals etc.) that can be seen as occasional ritual celebrations of society, constructed and transmitted by electronic media. This article is a preliminary study, employing the concept of ritual on a few extracts from two different empirical studies, one from Brazil and one from Denmark. First we present some empirical examples in order to introduce the main concerns of the article. Tlien we define ritual as a primarily anthropological concept and consider its qualifications as an analytical tool in media studies. We then go on to a critical reading of some of the ways the concept of ritual is applied in media research, and, finally, we re-analyze our empirical examples in order to point out further theoretical and analytical perspectives.